THE The Effect of Mixing Plastic Pyrolysis Oil with Pertamax and Variation Of Ignition Timing on Performance and Emissions - Naufal Hana Rizqullah; Monasari, Ratna; Utami Handayani, Sri; Aditya, Candra (Evrimata: Journal of Mechanical Engineering, 2024)
One source of energy that has not been utilized optimally is waste. One of the abundant waste materials is plastic waste. Processing plastic waste in the form of plastic pyrolysis oil affects the performance and emissions of motor vehicles when mixed with Pertamax fuel, as well as variations in ignition timing. The purpose of this research is to determine the influence of changes in ignition timing on engine power, as well as to investigate the impact of using Pertamax mixed with pyrolysis fuel results on engine power. The fuel mixture is prepared based on volume ratios (0%, 10%, 20%, 30%, 100%) of pyrolysis to gasoline, with engine speeds ranging from 6500 to 9000 rpm. The experiment results, when the ignition timing was set at 6⁰, 8⁰, and 10⁰, there was a slight decrease in power and less stable results in some engine speed.